2018
DOI: 10.20867/thm.24.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cognitive Style of a Manager in the Development of Tourism Companies’ Dynamic Capabilities

Abstract: Purpose -The purpose of this paper is to investigate the relationship between cognitive styles of managers working in tourism companies and dynamic capabilities of these companies. Design -The research relies on a quantitative questionnaire. Methodology -To answer the research question, the bivariate (Pearson) correlation was applied. A number of 268 answers from people working in tourism were received. Findings -We found a positive correlation between different dimensions of dynamic capabilities of tourism co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
(53 reference statements)
1
12
0
4
Order By: Relevance
“…Literature has revealed various leadership competences that facilitate the adoption of organizational innovation within organizations. Krupskyi and Grynko (2018) found that cognitive competence of leaders positively affected the implementation of organization innovation. Middle managers' metacognitive culture intelligence was found to be a driver of firm's innovation in Berraies's (2019) study.…”
Section: Leadership Competences and Organizational Innovationmentioning
confidence: 99%
“…Literature has revealed various leadership competences that facilitate the adoption of organizational innovation within organizations. Krupskyi and Grynko (2018) found that cognitive competence of leaders positively affected the implementation of organization innovation. Middle managers' metacognitive culture intelligence was found to be a driver of firm's innovation in Berraies's (2019) study.…”
Section: Leadership Competences and Organizational Innovationmentioning
confidence: 99%
“…Second, this research is one of few pioneering studies of the dynamic capabilities at the firm level in the tourism sector of an emerging economy. Although much important work has been carried out on examining dynamic capabilities in hospitality settings, such as Pattanasing et al ( 2021 ) and Krupskyi and Grynko ( 2018 ), several questions remain for the rest of the tourism sector. For example, a study by Nieves and Haller ( 2014 ) examines dynamic capabilities in the Italian hotel sector.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to say about the emotional component of ethics and law (Petra_ zycki, 1955;Pavlova and Bobyl, 2018). A man always feels certain emotions (positive or negative) regarding ethical and legal reality (Frijda, 2001;Benartzi and Thaler, 2013;Grynko et al, 2017), which has an impact on a decision-making process in many spheres of public life (Barreto, 2006;Mynhardt and Plastun, 2013;Khmarskyi and Pavlov, 2017;Sardak et al, 2017;Velychko and Velychko, 2017;Krupskyi and Grynko, 2018).…”
Section: Metamorphosis Of Practical Mind In Kant's Ethical and Legal Discoursementioning
confidence: 99%